Environmental drivers influencing the abundance of round sardinella (Sardinella aurita) and European sprat (Sprattus sprattus) in different areas of the Mediterranean Sea - DE FELICE, ANDREA; IGLESIAS, MAGDALENA; SARAUX, CLAIRE; BONANNO, ANGELO; TIČINA, VJEKOSLAV; LEONORI, IOLE; VENTERO, ANA; HATTAB, TAREK; BARRA, MARCO; GAŠPAREVIĆ, DENIS; BIAGIOTTI, ILARIA; BOURDEIX, JEAN-HERVE; et al. (Mediterranean Marine Science, 2021)
Data on Sardinella aurita (round sardinella) and Sprattus sprattus (European sprat) in the Mediterranean Sea are limited due to their scarce commercial interest, at least in European countries. Yet, these two small pelagic fish, sitting at opposite ends of the thermal range, could be interesting sentinel species to monitor the effects of climate change in the basin. Using the Mediterranean International Acoustic Surveys (MEDIAS) – the most extensive source of information on these species – we analyzed their biomass in several geographical subareas of the central and western Mediterranean Sea in relation to satellite-derived environmental parameters. Our findings highlight that the S. aurita biomass responded to temperature, salinity, chlorophyll concentration and sea level anomaly, depending on the GSA examined, whereas the S. sprattus biomass correlated significantly with salinity in GSA 6, with salinity and chlorophyll concentration in GSA 7, and with sea level anomaly in GSA 17. These data widen our knowledge of the factors that contribute to the ecology of these species. Further studies of their spatial distribution and of their interactions with other small pelagic species, predators and prey are needed to depict a more comprehensive scenario.